2008
DOI: 10.1097/inf.0b013e3181684d52
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Persistence

Abstract: Several studies have described a clear association between respiratory syncytial virus (RSV) lower respiratory tract infection in infancy and the subsequent development of persistent wheezing in children. Using the mouse model we demonstrated that RSV induces long-term airway disease characterized by chronic airway inflammation and airway hyperreactivity (AHR). The RSV murine model offers great advantages to study the immunopathogenesis of RSV-induced long-term airway disease. Mice can be challenged with aeros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 16 publications
3
19
0
3
Order By: Relevance
“…HMPV shares epidemiological and clinical traits with RSV causing clinical symptoms ranging from upper respiratory tract disease to severe bronchiolitis and pneumonia and may exacerbate chronic obstructive pulmonary disease (6,12,48,51,57,61,73). RSV has been shown to persist in a variety of cells and animal models (10,17,37,60,61,66,72), and infection with RSV has been shown to induce acute and chronic airway disease correlated with pulmonary function abnormalities (23,52). Since HMPV can cause persistent infection (1, 2, 32), this suggests that persistence may be a potential mechanism that could contribute to post-bronchiolitis disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HMPV shares epidemiological and clinical traits with RSV causing clinical symptoms ranging from upper respiratory tract disease to severe bronchiolitis and pneumonia and may exacerbate chronic obstructive pulmonary disease (6,12,48,51,57,61,73). RSV has been shown to persist in a variety of cells and animal models (10,17,37,60,61,66,72), and infection with RSV has been shown to induce acute and chronic airway disease correlated with pulmonary function abnormalities (23,52). Since HMPV can cause persistent infection (1, 2, 32), this suggests that persistence may be a potential mechanism that could contribute to post-bronchiolitis disease.…”
Section: Discussionmentioning
confidence: 99%
“…RSV and HMPV genome have been detected in chronic obstructive pulmonary disease patients (24,25,49,61,76,78), a feature suggestive of persistent infection. In the mouse model, RSV has been shown to induce long-term airway disease characterized by chronic airway inflammation and airway hyper-reactivity, where 42 days after RSV infection reverse transcription-PCR (RT-PCR) indicated the presence of viral RNA in the lower respiratory tract, and the presence of genomic RNA persisted for months after infection (52). These findings are consistent with other findings that RSV persists in the lungs of guinea pigs 60 days after the resolution of acute bronchiolitis (17,37), and the observation of RSV latency and persistence in the lungs of BALB/c mice despite T-cell immunity (60).…”
mentioning
confidence: 99%
“…Among the 1% to 3% of infants hospitalized with RSV bronchiolitis, up to 90% of children have experience 2 or more wheezing episodes, and almost 50% will be given a diagnosis of asthma by the age of 6 years (1, 2). Several studies, including epidemiology studies and animal model studies, have shown that RSV persistence in the lung of the host after RSV infection was related to long-term airway hyperresponsiveness (AHR) and inflammation (3)(4)(5). However, the mechanisms of these sequelae are poorly understood.…”
mentioning
confidence: 99%
“…Taken further, RSV has clearly been shown to cause persistent, noncytolytic infection of epithelial cells in vitro [28]. RSV persistence, characterized by continuous, low-level replication of infectious virus, has been described in vivo, first in a model in which cotton rats were immunosuppressed with cyclophosphamide [29], and subsequently in immunocompetent guinea pigs [30] and in mice [31,32]. There is also evidence consistent with RSV persistence in humans, best characterized in the setting of adult patients with chronic obstructive pulmonary disease [33].…”
Section: Rsv Infections In Vitro Versus In Vivomentioning
confidence: 99%